3D printable, tough, magnetic hydrogels with programmed magnetization for fast actuation. Issue 44 (26th October 2021) - Tang, Jingda; Sun, Bonan; Yin, Qianfeng; Yang, Meng; Hu, Jian; Wang, Tiejun
Abstract : A microgel-reinforced magnetic hydrogel embedded with hard magnetic particles has been prepared for fast and complex shape changing. Abstract : Magnetic hydrogels have demonstrated great potential in soft robots, drug delivery, and bioengineering, and their functions are usually determined by the deforming capability. However, most magnetic hydrogels are embedded with soft magnetic particles ( e.g. Fe3 O4 ), where the magnetic domains cannot be programmed and retained under external magnetic fields. Here, we present a strategy to prepare a microgel-reinforced magnetic hydrogel, embedded with hard magnetic NdFeB particles. These magnetic hydrogels show outstanding mechanical properties (ultimate stretching ratio >15 and fracture toughness >15 000 J m −2 ) and fast actuation speed under external magnetic fields. We use direct ink writing to fabricate magnetic hydrogels with sophisticated geometry and program their magnetization to achieve complex deformations. Fast, reversible, shape-changing structures have been demonstrated with printed magnetic hydrogels. It is hoped that this material system of hard magnetic hydrogels can open opportunities for wide applications.